Determining the effects of total productive maintenance system on production system using a Kaizen approach implementation - Erdem, I; Onut, S; Taskin, S (C S R E A PRESS, 2003)
More recently, improved technology and the increased sophistication of maintenance personnel have led some companies to replace reactive approach with newer maintenance strategies like TPM. While these strategies require greater commitments in terms of training, resources and integration, they are also expected to provide higher levels of equipment and plant performance. In order to achieve this aim and support these kinds of maintenance activities, continuous improvements in products and processes should be widely recognized This paper reports the results of a study of the relationship between TPM and Kaizen. Based on our analysis, we have proved that there is a strong positive relationship between these concepts.
Keywords: total productive maintenance; Kaizen; total quality management; Computer Science